2006
DOI: 10.1038/sj.bjc.6603262
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical estimation of cell cycle phase in laryngeal neoplasia

Abstract: We previously developed an immunohistochemical method for estimating cell cycle state and phase in tissue samples, including biopsies that are too small for flow cytometry. We have used our technique to examine whether primary abnormalities of the cell cycle exist in laryngeal neoplasia. Antibodies against the markers of cell cycle entry, minichromosome maintenance protein-2 (Mcm-2) and Ki67, and putative markers of cell cycle phase, cyclin D1 (G1-phase), cyclin A (S-phase), cyclin B1 (G2-phase) and phosphohis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 33 publications
(41 reference statements)
2
13
0
1
Order By: Relevance
“…They found that MCM2 protein is expressed in the same cells as cyclins A and D1, and also in some cells expressing cyclin B1 and phosphorylated histone H3. This fact suggests that MCM2 proteins are present during all phases of cell cycle, but their strongest expression is observed in phase G1 and S (51). MT-I/II, similarly to Ki-67, are associated with cell proliferation process.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that MCM2 protein is expressed in the same cells as cyclins A and D1, and also in some cells expressing cyclin B1 and phosphorylated histone H3. This fact suggests that MCM2 proteins are present during all phases of cell cycle, but their strongest expression is observed in phase G1 and S (51). MT-I/II, similarly to Ki-67, are associated with cell proliferation process.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still a lack of analysis of MCM protein expression and the prognostic significance in LsCC. The importance of MCM2 protein as a prognostic marker in LSCC was described in two studies (27,51), whereas the significance of MCM3 and MCM7 in LSCC has not been reported so far. Expression of MCM7 was in turn evaluated in other cancers of head and neck area, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…32 Labeling index with anti-MCM antibodies is correlated with Ki-67 but is significantly higher. 9,46 Indeed, in contrast with Ki-67, MCM proteins are expressed in early G1 and are later downregulated when the cells adopt a terminally differentiated phenotype. 14,31 MCMs were shown to be useful markers of proliferation 5,7,[20][21][22]30 In the field of neuropathology, few studies have analyzed MCM3 and MCM7 in astrocytoma 15,16,49 and MCM2 in oligodendroglioma.…”
Section: Proteinmentioning
confidence: 95%
“…The overexpression of the EGF receptor is also an early event in carcinogenesis (Rubin Grandis et al, 1998). Amplification and overexpression of the CCND1 gene, encoding cyclin D1 is a common late event in HNSCC formation (Michalides et al, 1995;Izzo et al, 1998;Chatrath et al, 2006). Our findings suggest that the upregulation of the OPN/CD44v6 axis is an additional early event during the progression of laryngeal dysplasia.…”
Section: Discussionmentioning
confidence: 64%